Anti-fracking campaigns in the United Kingdom: the influence of local opportunity structures on protest. (4th March 2023) - Garland, Joshua; Saunders, Clare; Olcese, Cristiana; Tedesco, Delacey
ABSTRACT: Hydraulic fracturing ('fracking') was a controversial issue in the United Kingdom that sparked national and community-led groups to organise protest mobilisations. To date, however, the social science literature has largely focussed upon general anti-fracking discourse rather than on the physical, community-led mobilisations that emerged from the frustrations of people directly affected at a local level by threats to their community. This paper develops and applies a novel conceptualisation of political opportunity structures at the nexus of the national and local levels to more fully explore the usually overlooked role of local-level structures in interaction with the national level in shaping protest. It uses protest event analysis with data derived from two key activist-specific sources. The analysis draws on data from over 1, 400 protests occurring across 69 counties from 2011 to 2019. In so doing, this paper observes and accounts for variance in the form and frequency of community-led anti-fracking protest events within and between different areas of England across the life course of the protest episodes. This paper finds that trends in protest frequency and form over time correlate to shifts in opportunity structures, particularly regarding local and national-level interactions, and that this can be usefully conceptualised through a local-national-state-nexus.